Research on quantum key distribution technology in intelligent substation - Xiaopeng YANG; Haitao CHEN; Lichen MEI; Pengzhan WANG (Dianxin kexue)
In order to improve the security of the communication data of the power system,the feasibility of the application of quantum key distribution technology in the monitoring system of the intelligent substation was analyzed and demonstrated by combining the state of quantum key distribution technology and intelligent substation monitoring system.The technical scheme,intelligent substation monitoring system combined with quantum key distribution was put forward.On the premise of using the existing power communication system framework,the networking idea of intelligent substation monitoring system and quantum key distribution technology was presented,which was“quantum key + power vertical encryption authentication gateway”.And the network scheme was verified and analyzed,which proved the stability and feasibility of the networking scheme in practical application.Therefore,no need to adjust the existing communication network framework,the application scheme can be realized on a large scale.